Melatonin regulates oxidative stress to delay senescence in Hemerocallis fulva L. - Haris Yousuf Lone; Moonisah Aftab; Wajahat Waseem Tantray; Aijaz A. Wani; Mohamad Arif Zargar; Inayatullah Tahir (Ornamental Horticulture)
Melatonin has emerged as a potent plant growth regulator, significantly enhancing the postharvest quality of horticultural products. Structurally analogous to the plant hormone indole-3-acetic acid, it regulates key processes like seed germination, growth, flowering and defense against abiotic stresses. Its powerful antioxidant properties make it an effective free radical scavenger, boosting plant resilience to oxidative stress and positioning it as an innovative phytohormone for postharvest treatments. The current study explores the efficacy of melatonin in delaying senescence in detached scapes of Hemerocallis fulva. Scapes were harvested when the most mature bud was one day before anthesis and treated with different concentrations of melatonin (40, 80, 120, and 160 µM). Results indicate that 120 µM melatonin treatment significantly delayed senescence, extending the vase life of the flower scapes (12 days) relative to untreated controls (7 days), which showed accelerated senescence. Melatonin application was associated with enhanced antioxidant enzyme activity, reduced lipoxygenase activity and diminished hydrogen peroxide (H2O2) levels, collectively alleviating oxidative stress. Furthermore, melatonin enhanced the content of soluble proteins, phenols, sugar fractions and proline content within the tepal tissues. The treatment also effectively suppressed bacterial proliferation and improved solution uptake in the flower scapes. These findings suggest that melatonin modulates the senescence of H. fulva by orchestrating oxidative stress responses and enhancing postharvest quality, offering a holistic and innovative approach to postharvest management.